Exploring high-penetration electric vehicles impact on urban power grid based on voltage stability analysis. (1st May 2020) - Lyu, Lin; Yang, Xinran; Xiang, Yue; Liu, Junyong; Jawad, Shafqat; Deng, Runqi
Abstract: Electric vehicles (EVs) have received significant attention in recent years. The high penetration of EVs increased the charging load in the distribution network, which has an enormous impact on "transportation and power grid" coupled energy networks. This paper developed the models and methods to evaluate the capacity of electrical energy supply based on voltage stability in the worst charging case scenario, under the existing coupled network. An optimization method with transportation network constraints is proposed to find the worst charging case scenario. In addition, the mobility of EVs is considered to calculate the load margin and the maximum number of EVs charging that a given grid can support in the critical situation. The method and model are simulated by test cases, which provide a perspective for realizing the EVs integration capacity limitation in urban areas considering the coupling relationship between transportation and power grids. Finally, the impact of charging location and route choice in the voltage margin limitation is emphasized. Highlights: A model for generating the worst charging scenario is proposed. A voltage stability analysis considering EVs' integration is proposed. The transportation and power grid are coupled and modeled. The allowable maximum number of EVs is calculated.